2019
DOI: 10.1109/access.2019.2957205
|View full text |Cite
|
Sign up to set email alerts
|

How the Type of Job Position Influences Technology Acceptance: A Study of Employees’ Intention to Use Mobile Technologies for Knowledge Transfer

Abstract: The acceptance of mobile technologies by employees is critical to their successful implementation in the workplace for competence development. Consequently, the type of job position (TJP) held was proposed as a new technology acceptance moderator and its significance verified. To examine this new moderator's role in explaining employees' intention to use technology, particularly mobile devices and applications for knowledge transfer, an extended Unified Theory of Acceptance and Use of Technology (UTAUT) model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…Hypothesis H2, positing that BI in FinTech Payment Systems is substantially positively affected by EE, is corroborated. Recent post-COVID-19 research aligns with these results, highlighting the significance of technology's ease of use and adaptability in shaping business conduct and decision-making processes [33], [55]. Research conducted by sources [32], [56], and [57] reveals a strong correlation between business expectations and the inclination towards technology use, particularly in a fast-changing digital environment.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Hypothesis H2, positing that BI in FinTech Payment Systems is substantially positively affected by EE, is corroborated. Recent post-COVID-19 research aligns with these results, highlighting the significance of technology's ease of use and adaptability in shaping business conduct and decision-making processes [33], [55]. Research conducted by sources [32], [56], and [57] reveals a strong correlation between business expectations and the inclination towards technology use, particularly in a fast-changing digital environment.…”
Section: Discussionmentioning
confidence: 66%
“…The belief that a technology can be employed effortlessly and with little difficulty substantially impacts users' initial readiness to embrace it. Nevertheless, as users gain familiarity with the technology and master its navigation, the significance of effort expectancy in influencing ongoing usage tends to wane over time [32], [33]. The argument posits that as a user's proficiency with the technology grows, the initial emphasis on ease of use diminishes in significance [34], [35].…”
Section: Effort Expectancy (Ee)mentioning
confidence: 99%
“…The results corroborate with Senge (1990), that most organizations are focused on the control of the individual, demanding more obedience than their creative capacity and this reality makes organizational learning an arduous and often conflicting task. In this sense, several authors argue that companies should develop shared visions, group learning and systemic thinking (CARVALHO et al, 2016;MATTIODA;DAUGHERTY, 2007;KUCIAPSKI, 2019;YANG;JIANG;ZHAO, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The IDTGIT inspired the script of semistructured questions. Previous studies (Kuciapski, 2019;Cimini et al, 2020) have shown that the type of job females have impact their use of IT. Job-type information was not collected because we understand that the mobility routine and the way of using the mobility apps had already captured a possible influence of job type in the urban mobility context.…”
Section: Data Collectionmentioning
confidence: 99%